Overexpressing superoxide dismutase 2 induces a supernormal cardiac function by enhancing redox-dependent mitochondrial function and metabolic dilation. (November 2015) - Kang, Patrick T.; Chen, Chwen-Lih; Ohanyan, Vahagn; Luther, Daniel J.; Meszaros, J. Gary; Chilian, William M.; Chen, Yeong-Renn
Abstract: During heightened cardiac work, O2 consumption by the heart benefits energy production via mitochondria. However, some electrons leak from the respiratory chain and yield superoxide, which is rapidly metabolized into H2 O2 by SOD2. To understand the systemic effects of the metabolic dilator, H2 O2, we studied mice with cardiac-specific SOD2 overexpression (SOD2-tg), which increases the H2 O2 produced by cardiac mitochondria. Contrast echocardiography was employed to evaluate cardiac function, indicating that SOD2-tg had a significantly greater ejection fraction and a lower mean arterial pressure (MAP) that was partially normalized by intravenous injection of catalase. Norepinephrine-mediated myocardial blood flow (MBF) was significantly enhanced in SOD2-tg mice. Coupling of MBF to the double product (Heart Rate × MAP) was increased in SOD2-tg mice, indicating that the metabolic dilator, "spilled" over, inducing systemic vasodilation. The hypothesis that SOD2 overexpression effectively enhances mitochondrial function was further evaluated. Mitochondria of SOD2-tg mice had a decreased state 3 oxygen consumption rate, but maintained the same ATP production flux under the basal and L-NAME treatment conditions, indicating a higher bioenergetic efficiency. SOD2-tg mitochondria produced less superoxide, and had lower redox activity in converting cyclic hydroxylamine to stable nitroxide, and a lower GSSG concentration. EPR analysis of the isolated mitochondria showed a significant decrease in semiquinones at the SOD2-tg Qi site. These results support a more reductive physiological setting in the SOD2-tg murine heart. Cardiac mitochondria exhibited no significant differences in the respiratory control index between WT and SOD2-tg. We conclude that SOD2 overexpression in myocytes enhances mitochondrial function and metabolic vasodilation, leading to a phenotype of supernormal cardiac function. Graphical abstract: Highlights: Gene delivery of SOD2 is widely applied to pre-clinical studies. Cardiac SOD2 overexpression enhances mitochondrial ATP/O ratio and reductive status. Cardiac SOD2 overexpression boosts metabolic vasodilation and myocardial perfusion. SOD2 overexpression in myocytes prevents L-NAME induced myocardial injury. SOD2 overexpression in myocytes improves overall cardiac function.